CHEMISTRY CONCEPTS IN NANOCELLULOSE ISOLATION AND ITS POTENTIAL FOR GREEN CHEMISTRY LEARNING - Hernani, Hernani; Fauzi, Billy Oktora Abdillah; Mudzakir, Ahmad (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
As a plant that is easy to grow, banana tree (Musa spp.) is an abundant tree in tropical countries. Banana tree is only able to bear fruit once in its lifetime and the waste of banana pseudo-stems are also existed in a large number. The cellulose content in the banana pseudo-stems can be utilized as a source of raw material for the manufacture of nanocellulose. This study aims to develop teaching strategy which introduce the process of nanocellulose isolation from banana pseudo-stem through a dissolve method using ionic liquid. The research method is the content analysis using the content validation format as the research instrument. The isolation process involves several school chemistry concepts as such as water evaporation, hydrolysis process, factors influencing reaction rate, intermolecular interaction, and colloid. Thus, this context has a potential to be integrated into school chemistry learning. Beside it, this context also has a potential to introduce the principles of green chemistry except catalysis principle.